OROPHARYNGEAL CANDIDIASIS: COMPARISON OF CLINICAL CHARACTERISTICS OF ACUTE AND CHRONIC COURSE - Ismatova K.A.,; Sabirova Sh.B., (Central Asian Journal of Medicine, 2025)
Oropharyngeal candidiasis (OPC) is one of the most common fungal infections of the oral mucosa, pharynx and larynx caused by yeast-like fungi of the genus Candida. Candida albicans remains the most common pathogen, but the clinical significance of other species (C. glabrata, C. tropicalis, C. parapsilosis) is increasing. The aim of this review is to summarize current data on the clinical characteristics of acute and chronic course of OFC, analysis of risk factors, diagnostic methods and approaches to therapy. The importance of immune status, background diseases and iatrogenic factors in the pathogenesis of the disease is considered, and modern classification approaches, differential diagnostics and therapeutic strategies are presented. The need for an individualized approach and preventive measures to prevent relapses is substantiated.